Pelatihan Pembuatan Media Konversi Satuan Berat Bagi Mahasiswa - Astuti; Dewi Puji Rahayu; Karlina Wong Lieung; Paustina Ngali Mahuze; Bernadetha Rizki Kaize; Mega Suteki; Retno Wuri Sulistyowati; Bhujangga Ayu Putu Priyudhahari; Paskha Marini Thana; Rival Hanip; Sri Hanipah (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Training is a form of Community Service or Pengabdian Kepada Masyarakat (PKM) carried out by lecturers. The target of the training is students with weight conversion material. The stages carried out are taking care of the PKM implementation permit, preparing the place as well as the tools and materials needed in the training, and implementing PKM. Weight conversion is interpreted as the weight of units between units having the same value. Weight conversion must be mastered by students as prospective teachers so that media creation training is needed. The training was held in March 2025 at Building 1.3, Musamus University. The results of the weight conversion training were that students were able to use weight conversion media and explain the conversion method in detail. The benefits obtained were that lecturers could share knowledge and experience in developing weight conversion media; for students, the benefits obtained were being able to make weight conversion media, becoming one of the media used when teaching, increasing creativity, and better communication skills.